Improving hydrodynamic cavitation using newer surface-coated cavitation reactors - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2023)
Surface-coated cavitation devices, vortex diode (SCVD) have been reported for the first time for enhancing efficiency of hydrodynamic cavitation (HC). Two surface-coated cavitation reactors using coating of copper and nickel (-50 mu m) were evaluated, also comparing results with conventional reactor vortex diode. The proof of concept is successfully demonstrated for complete degradation of two model organic pollutants, antibioticscephalexin (CFX) and ciprofloxacin (CIP). The surface-coated reactors provide dual activity, and the catalytic effect is highly pronounced with process intensification using H2O2 and/ or pH alternations. Integration of SCVD, pH and H2O2 was the most effective strategy. Complete degradation of the antibiotics was achieved within minutes with H2O2 (-1000 molar ratio) for both Cu and Ni-surface-coated cavitation reactors compared to lower degradation of-19% for CFX and-37% for CIP using only HC. An excellent enhancement of over 300% for CFX degradation at pH 11 and-170% for CIP degradation at pH 4 was obtained. Huge enhancements in per-pass degradation and cavitational yields (up to 400 times) clearly highlight the utility of the surface-coated cavitation reactors in various applications and for cost-effectiveness.(c) 2023 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrodynamic cavitation; Oxidation; pollution; Reactor; Technology; Wastewater treatment